Macroeconomic determinants of unemployment in Nepal - Acharya, Khubi Ram (NCC Journal, 2020)
The relationship between unemployment and macroeconomic variables is complex, but it is generally accepted that increasing GDP, trade, and expansionary monetary policy lead to a decrease in the rate of unemployment. This paper tests this hypothesis for Nepal using time series data from 1991 to 2021 and a simple time series model. It is found that the increase in GDP, trade openness, money supply, and the rate of inflation decrease the unemployment rate in Nepal. These results have huge policy implications.